Ordering of image processing techniques to enhance wood grain images / Norfaizah Jamil - Jamil, Norfaizah (2008)
Wood is the most God's precious gift to mankind, remains to this day a necessity to the comfort life, and for many livelihood itself. The complexity of wood grain is the main reason why is it so hard to do wood classification. Therefore, the images of wood grain needed to be enhancing for further process. In order to enhance the image, some image processing techniques be used. Good ordering of image processing techniques will ensure the end result is benefit to be used for classification or others. The objective of this study is to study the three image processing techniques which are blurring technique, brighten technique and sharpen technique as well as the best ordering of those techniques.